Detrusor Overactivity After Partial Bladder Outlet Obstruction Is Associated With High Urinary Adenosine Triphosphate Levels in Female Wistar Rats - Luís Vale; Francisco Cruz; Ana Charrua (International Neurourology Journal, 2024)
Purpose Bladder outlet obstruction (BOO) commonly causes detrusor overactivity (DO). In this study, a post hoc analysis of previous obtained data, we investigate if DO occurring in initial phases of BOO is associated with changes in urinary adenosine triphosphate (ATP) levels. Methods Adult female Wistar rats were submitted to partial BOO (pBOO) or to sham obstruction. Cystometry was performed at 3 or 15 days after pBOO and saline voided was collected for ATP determination. Normality was tested using Shapiro-Wilk test. The mean frequency of voiding contractions (VCs) of the sham-operated animals at 15 days after surgery, plus or minus 3 standard deviations, was used to represent the normal range. Statistical analyses were performed using the chi-square and Mann-Whitney tests. Results DO was indicated by a VC frequency greater than or equal to 0.9 VCs/min. DO was observed in 63% of animals at 3 days and in 33% at 15 days following pBOO. ATP levels were significantly higher in rats with DO compared to those without DO. Conclusions The DO phenotype, occurring in the initial phases of BOO, is associated with comparatively high urinary ATP levels.